Learning Management Systems in Universities of Medical Sciences of Iran and Several Developed Countries - Majid Zare-Bidaki; Sajad Sadrinia; Ali Rajabpour-Sanati (Kerman University of Medical Sciences, 2015)
Background & Objective: The core of each WBT system is an online software called learning management system (LMS) The existence of such a system in each university is the minimum requirement for the application and development of WBT methods The present study aimed to investigate the frequency of LMS usage in Iranian medical universities in comparison with the universities of developed countries   Methods: This descriptive crosssectional analysis was performed in 2014 The study population consisted of Iranian medical universities and the universities of 4 developed Englishspeaking countries including USA Canada Australia and UK From among the Iranian universities a total of 52 universities were selected using the census method Moreover 58 universities were randomly selected from among 450 wellknown universities of developed countries The data from LMS of Iranian medical universities were collected through visiting university websites telephone calls and in some cases facetoface interviews The data were analyzed by descriptive methods   Results: Of the 52 Iranian universities of medical sciences 33 universities (635%) did not have any LMSs for delivery courses in academic degree programs Of the 19 universities (365%) with LMSs Moodle ATutor Docebo and nativedesigned LMSs were found in 11 4 1 and 3 universities respectively In addition 16 Iranian universities used open source LMSs and 3 used commercial LMSs All 58 (100%) universities of developed countries used LMSs for delivery courses in their academic degree programs Blackboard Moodle Canvas Desire2learn and Sakai were used in 30 13 8 1 and 1 foreign universities respectively Moreover 2 universities were in transition stage and 3 universities used the Mooc system   Conclusion: Iran universities showed a considerable difference from universities in developed countries in terms of frequency of LMS usage Educational and IT administrators in Iran should fill this gap especially at high ranking universities